FACIAL PALEOGEOGRAPHIC CONDITIONS FOR THE FORMATION OF PALEOCENE-LOWER EOCENE DEPOSITS OF FERGANA DEPRESSION - Pulatjon Sultonov , Bakhodir Meliboyev , Farkhod Chulliev, Mansur Ruziev (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
As result of facial-paleogeographic studies of the Paleogene deposits of the Fergana depression are distinguished underwater delta, wave-cut, shallow-bay (lagoon) and centraldesilting facial belts. The article gives a detailed description of the lagoon facies with their separation into 4 types, which can be the criteria for the prospecting and exploration of nonmetallic minerals, such as palygorskite clays, dolomites and gypsum.